Modul Digital Berbasis Model Pembelajaran Value Clarification Technique (VCT) untuk Mengembangkan Karakter Antikorupsi Mahasiswa - Sri Yunita; Sri Hadiningrum; Sugiharto Sugiharto (Universitas Negeri Medan, 2021)
This study aims to: 1) develop a digital module based on the VCT learning model for anti-corruption learning; 2) to analyze the impact of implementing a digital module based on the VCT learning model on the anti-corruption learning outcomes of students majoring in Citizenship education, FIS UNIMED. This study uses a development research method using stages adapted from the Borg & Gall model, namely: 1) a preliminary study; 2) research planning; 3) initial product development; 4) field trials I (limited); 5) revised test results I; 6) field trials II (wider); 7) revision of trial results II; 8) due diligence; 9) revision of feasibility test results and 10) dissemination and socialization of the final product. The research was conducted in the Department of Citizenship Education, Faculty of Social Sciences, UNIMED. The expected outputs are 1) Digital Module Based on VCT Learning Model, 2) Application of VCT-based digital module on Anti-Corruption material increases student learning outcomes by 19.2%.